Anticoagulant for treatment and prophylaxis of venous thromboembolism patients with renal dysfunction: A systematic review and network meta-analysis - Fan, Guohui; Wang, Dingyi; Zhang, Meng; Luo, Xufei; Zhai, Zhenguo; Wu, Sinan (Frontiers in Medicine, 2022)
Objective: To compare the efficacy and safety for particular regimen and dosage in venous thromboembolism (VTE) patients with renal insufficiency. Methods: English-language searches of Pubmed, EMBASE and Web of Science (inception to May, 2021). RCTs evaluating anticoagulants for VTE treatment at acute phase, extension phase and for VTE prophylaxis in patients with renal insufficiency and reporting efficacy (death, recurrence, or occurrence of VTE) and safety (bleeding) outcomes were selected. The methodological quality of each study included was assessed at the outcome level using the risk-of-bias assessment tool developed by the Cochrane Bias Methods Group. Results: Twenty-one trials that involved 76,574 participants and 8,972 (11.7%) patients were enrolled, including 10 trials on VTE treatment in acute phase (3 to 12 months), 4 trials on VTE treatment in extension phase (6 to 36 months) and 7 trials for VTE prophylaxis. For acute VTE treatment, compared with dabigatran etexilate, apixaban (RR 5.90, 95%CI 1.00-34.60) and rivaroxaban (RR 6.18, 95%CI 1.17-32.75) were significantly associated with increased risk of death or recurrence. For extension treatment of VTE, aspirin had the highest probability of the most effective and safest, followed by apixaban. For VTE prophylaxis, compared with enoxaparin, desirudin was associated with lower risk of VTE occurrence (RR 0.56, 95%CI 0.34-0.91), but had higher risk of bleeding than dabigatran etexilate. Conclusions: The network meta-analysis informs the optimal choice of anticoagulants and their particular dosage for treatment and prophylaxis of VTE patients comorbid renal insufficiency.